ANALISIS PERUBAHAN PERILAKU PADA MASYARAKAT DENGAN ADANYA PEMBUATAN BIOGAS DI 5 KECAMATAN KABUPATEN BOYOLALI: ANALYSIS OF BEHAVIORAL CHANGES IN THE COMMUNITY RESULTING FROM BIOGAS PRODUCTION IN 5 DISTRICTS OF BOYOLALI REGENCY - Surya Aditya Nuril Huda; Purwadi Purwadi; Aris Budi Prasetyo (Universitas Boyolali, 2026)
This study aims to analyze the social, economic, and environmental impacts of the implementation of a biogas program based on the Asset-Based Community Development (ABCD) approach in five sub-districts in Boyolali Regency. Using a participatory approach, the study involved 10 respondents who actively use biogas installations. Data were obtained through observation, interviews, and questionnaires. The results showed that the biogas program drove significant changes in energy consumption patterns, with 30% of respondents switching entirely to biogas, and 50% combining it with LPG. In addition, 80% of respondents used bio-slurry as organic fertilizer, which resulted in increased soil fertility and more efficient chemical fertilizer use. From an economic perspective, 50% of respondents managed to save up to 80% of their monthly energy costs, and 30% saved up to 100%. The program's satisfaction level reached 100%, with 80% stating they were very satisfied. The program also increased community environmental awareness through the utilization of livestock waste and emission reduction. These findings confirm that the ABCD approach is effective in building energy independence based on local potential and encouraging community behavioral changes towards sustainable